Comment on ‘‘Impact structures in Africa: A review’’ by Reimold and Koeberl [J. Afr. Earth Sci. 93 (2014) 57–175] - Acevedo, Rogelio Daniel (2014)
Reimold and Koeberl (2014) published a detailed account of the African impact record. In the same paper they refer (on page 67) to recent reports of an entire impact crater strewn field in the volcanic Bajada del Diablo area of Argentina, where many crater-like features have been related to impact but, to date, no conclusive pro-impact evidence – what-so-ever – has been recognized; arguing that they may be related simply to volcanic processes. Later in their paper (on page 87) Bajada del Diablo is dismissed as an impact feature because it does not conform to the established criteria in Reimold et al. (2014)